Spanish language teaching in Brazil: a historic construction - Rodrigues Da Cunha, Carolina Andrade (2021)
This study seeks to analyze the path of the methods used by Spanish teachers in Brazil, from their first mandatory appearance in the curricula, in 1942, to the present day, with the advancement of the Internet and Information and Communication Technologies, in order to understand the relationship between political and economic events and the history of education and curriculum. We seek to understand the reasons that led the Brazilian State to make the study of that language mandatory and reflect on the interference of historical development in the way this foreign language is taught, studying each of the applied teaching methods.